Differential Difficulties in Perception of Tashlhiyt Berber Consonant Quantity Contrasts by Native Tashlhiyt Listeners vs. Berber-Naïve French Listeners - Hallé, Pierre A.; Ridouane, Rachid; Best, Catherine T. (Frontiers in Psychology, 2016)
In a discrimination experiment on several Tashlhiyt Berber singleton-geminate contrasts, we find that French listeners encounter substantial difficulty compared to native speakers. Native listeners of Tashlhiyt perform near ceiling level on all contrasts. French listeners perform better on final contrasts such as fit-fitt than initial contrasts such as bi-bbi or sir-ssir. That is, French listeners are more sensitive to silent closure duration in word-final voiceless stops than to either voiced murmur or frication duration of fully voiced stops or voiceless fricatives in word-initial position. We propose, tentatively, that native speakers of French, a language in which gemination is usually not considered to be phonemic, have not acquired quantity contrasts but yet exhibit a presumably universal sensitivity to rhythm, whereby listeners are able to perceive and compare the relative temporal distance between beats given by successive salient phonetic events such as a sequence of vowel nuclei.